Evolution of Indonesian Islamic Intellectual Fashion in the Early 20th Century: A Visual Narrative Analysis - Soni Sadono; Brilindra Pandanwangi; Teddy Ageng Maulana; Danil Kasputra (RSF Press, 2023)
Throughout Indonesia's history, clothing has served multiple purposes, representing not only social status but also an individual's position in society. From the eras of Hindu-Buddhist influence to the advent of Islam and into the modern era, Indonesian attire has been a canvas colored by evolving customs and cultural shifts. As the 20th century began, a dynamic transformation in clothing styles emerged, spurred by the rise of Indonesian intellectuals in response to Dutch ethical policies. This change was evident among Indonesian Islamic intellectuals as well, where traditional robes and sarongs, once emblematic of Muslim attire, lost their primary significance. This study aims to delve into the fashion choices of Indonesian Islamic intellectuals during the early 20th century. Employing a historical research method comprising four stages—heuristics, criticism, interpretation, and historiography—the research seeks to uncover the influence of Western fashion on these intellectuals' clothing choices. The findings of this study illuminate how Western fashion elements such as suits, ties, hats, and shirts became commonplace among Indonesian Islamic intellectuals during this transformative period.